Implementation of Religious Character Education For students of Junior High School 12 Surabaya - Prihatin, Anna Aisyah; Yani, Muhammad Turhan; Setyowati, Raden Roro Nanik (International Journal of Emerging Research and Review, 2025)
Objective: This study analyzes the implementation of religious character education at Junior High School 12 Surabaya, focusing on the effectiveness of programs in shaping students' religious values. Religious character education, when consistently implemented, can foster individuals with high empathy, respect for diversity, and the ability to interact positively within their communities. Method: This research employs a descriptive qualitative approach, with data collected through in-depth interviews with the vice principal, religious teachers, students, and school document analysis. The study was conducted at Junior High School 12 Surabaya, located on Jl. Ngagel Kebonsari, Wonokromo District, Surabaya City. Results: The research results show Implementation of religious values at Junior High School 12 Surabaya has shown positive results, even though there are still some obstacles. Programs such as KKS and Jum'at Taqwa, as well as the habituation and role model approach, have succeeded in strengthening students' religious character. Novelty: What is new in this study is the focus on implementation of religious values ​​at Junior High School 12 Surabaya has succeeded in creating a religious and conducive educational environment, which supports the development of students' attitudes, behavior and personality in accordance with religious values.